Temporal and spatial dynamics in the extraction of non-timber forest products in the Northern Bolivia Amazon - Dijkman, W.; Stoian, D.; Henkesmans, A.B.; Assies, W.; Boot, R.G.A. (1998)
For more than a century, northern Bolivia has had a tradition of commercial forest exploitation. For several decades into the twentieth century, the extraction of rubber and Brazil nuts was combined with subsistence agriculture, resulting in an agro-extractive cycle that fostered a sedentary lifestyle of forest dwellers. The extraction of rubber and Brazil nuts used to be organized in a debt-peonage system, often leaving extractivists in debt to the patron. The decline of the Bolivian rubber market during the 1980s induced the breakdown of the agro-extractive cycle. Most people left the patron-controlled extraction areas (barracas), and either established themselves as farmers in independent communities close to urban areas or migrated to the cities where the processing of forest products had increased job opportunities. About half the Brazil nut collectors are now seasonal migrants, mainly from the cities. Depending on access to land, forest resources, and markets, extraction-based income can contribute to more than 50% of the overall household income, especially in the more remote forest settlements. Some processing plants gain direct access to tbe Brazil nut resource base through vertical integration, thereby increasing their control of the production process. These large enterprises partly take over the role of the former patrons (e.q. on making advance payments to the Brazil nut collectors). The increasing demand for Brazil nuts and the increased in-country processing in Bolivia has benefited all participants in the production process, including the collectors. Especially the collectors from independent communities manage to get a higher price for the nuts they collect. Even so, an unequal exchange continues to be characteristic of many non-timber-forest-products-based (NTFP-based) production systems. In addition, more recent extractive activities (e.q. logging and palm-heart extraction) are threatened by depletion of the resource area. None of the extractive activities thus fulfills all the criteria of sustainable development